Hubungan Metode Pembelajaran Discovery terhadap Hasil Belajar Menggambar Bentuk Peserta Didik Sekolah Menengah Atas Negeri 1 Pollung - Yunniko Anrio Pandiangan; Sugito Sugito (Mahesa Research Center, 2021)
Study aims to determine whether there is a relationship between the discovery learning method and the results of learning to draw shapes.The population in this study were all students of class X SMA Negeri 1 Pollung who took shape drawing lessons with a total of 288 students and a sample of 40 people, namely each The class consists of 5 students with sampling using the Quota Sampling technique. This research method uses correlational research. The findings of this study indicate that there is a correlation between the ability to draw shapes with the discovery learning method (X1) with the results of learning to draw shapes (Y) = 30.20 for DK = n-2 = 38 α = 0.05 ttable = 1.684 turns out that > (30.20> 1.684), the ability to draw shapes using discovery learning method (X2) with the result of learning to draw shapes (Y) t _count = 3.46 for DK = n-2 = 38 α = 0.05 = 1.684 turns out that > (3.46> 1.684). The magnitude of the relationship between the ability to draw shapes (X_1) (X_2) with learning outcomes to draw shapes (Y) has a correlation of 0.98 and 0.49, and the contribution is 96% and 24%.